Ensuring just resilience to climate impacts: A framework for policy implementation - Stefano Ceolotto; Pranav Kakkar; Niall Farrell (The Economic and Social Research Institute (ESRI), 2024)
Just resilience is a conceptual framework to guide equitable, persistent and transformative adaptation to climate change impacts, ensuring that systems are robust and can shift when previous equilibria become unsustainable. Much research exists to define this concept, with much less instruction on how to incorporate these key principles into policy decision-making. In particular, much emphasis exists to consider the definition and application of concepts for countries categorised as being low and middle income economies, with less guidance for high income countries. This paper provides this insight, focussing on Ireland as a representative case study. We collate findings from the literature to provide a comprehensive definition and framework through which principles of use may be incorporated into the policy formulation process.
Keywords: 330; Klimawandel; Resilienz; Politische Entscheidung; Irland